A case-control study of reaction time deficits in a 3D virtual reality in patients with Post-COVID syndrome - Güttes, Moritz; Lucio, Marianna; Skornia, Adam; Rühl, Eva; Steußloff, Fritz; Zott, Julia; Mardin, Christian; Mehringer, Wolfgang; Ganslmayer, Marion; Michelson, Georg; Hohberger, Bettina (Scientific Reports, 2024)
Following the Coronavirus disease 2019 (COVID-19) pandemic, a large number of people continue to report Post-COVID symptoms (PCS). A wide variety of symptoms are described, including fatigue, post-exertional malaise and cognitive impairment. However, adequate objective diagnostic tests for PCS are not yet available. Since the neurotropism of SARS-CoV-2 could be a possible factor for cognitive impairment, the aim of this study was to clarify whether visual reaction time (RT) in a stereoscopic setting can be a marker in PCS diagnostics. The Virtual-Reality-Oculomotor-Test-System (VR-OTS) was used testing binocular vision in 9 gaze directions via stereoscopic stimuli displayed in a virtual reality (VR)-environment (disparity: 275″, 550″, 1100″) in 179 individuals: 130 patients with PCS and 49 healthy controls. The results from the generalized linear models indicated that both group membership (PCS vs. control) and covariates (age and sex) yielded statistically significant different RT across the models. Accounting for the effect of covariates a statistically significant difference of RT was observed between patients with PCS and controls (disparity 275″ p-value = 0.001; 550″ p-value = 0.001; 1100″ p-value = 0.003). Patients with PCS performed worse in RT in all gaze directions, respectively. Adjusting for the influence of covariates, correct responses (CR) differed significantly between patients with PCS and controls (disparity 275″ p-value < 0.001; 550″ p-value = 0.003; 1100″ p-value = 0.019). Statistically significant effects of covariates on RT were observed for sex (disparity 275″ p-value = 0.047; 550″ p-value = 0.012; 1100″ p-value = 0.005) and age (disparity 275″ p-value < 0.001; 550″ p-value < 0.001; 1100″ p-value < 0.001). However, regarding covariates, no significant effects were found for CR, except for age at disparity 275″ (p-value = 0.035). The present data suggested that the mentioned variables uniquely contributed to explain the variation of the response variable (RT, CR). RT and CR detecting 3D-stimuli in a virtual 3D- environment might offer novel functional diagnostic approaches in PCS.
CRIS-Team Scopus Importer:2024-11-29